PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPS) KELAS VI SDN 001 EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Maznah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research was the low mathematics learning outcomes of students. This could be seen from 28 students, of whom only 13 students (46.43%) achieved the Minimum Mastery Criteria (KKM), with an average score of 56.96. This study was a Classroom Action Research (CAR) conducted at SDN 001 Empat Balai, Kouk District, and was carried out in two cycles by applying the Think Pair Share (TPS) learning model. The purpose of this study was to improve students’ mathematics learning outcomes. The data used in this study included learning outcome data and teacher and student activity data. The results of the study indicated that the TPS learning model was able to improve students’ mathematics learning outcomes and learning activities. This was evidenced by the improvement in students’ learning outcomes in each cycle, where the initial data showed an average score of 56.96 with 13 students (46.43%) achieving mastery, which increased in Cycle I to an average score of 69 with 19 students (69.86%) achieving mastery, and further increased in Cycle II to an average score of 77.43 with 24 students (85.71%) achieving mastery. In addition, teacher activities also improved in each cycle, where in Cycle I Meeting I the score obtained was 14 (58.33%) in the low category, in Cycle I Meeting II the score increased to 16 (66.67%) in the sufficient category, in Cycle II Meeting I the score increased to 19 (79.16%) in the good category, and in Cycle II Meeting II the score reached 21 (87.50%) in the very good category. Student activities also showed improvement, where in Cycle I Meeting I the score obtained was 13 (54.16%) in the low category, in Cycle I Meeting II the score increased to 16 (66.67%) in the sufficient category, in Cycle II Meeting I the score increased to 18 (75.00%) in the good category, and in Cycle II Meeting II the score reached 22 (91.67%) in the very good category.